Interesting 54 months survival after platinum based induction chemotherapy regimen alone in a patient with T2N0M0 supraglottic carcinoma - Kezban Gürbüz, Melek; Çaklı, Hamdi; Dinçer, Murat; Ediz, Durmuş; Dündar, Emine; Özüdoğru, Erkan (ENT Updates, 2012)
The conventional treatment modalities are surgery and/or radiation therapy in patients with early stage squamous cell carcinoma of the supraglottic larynx. In the literature, there are different opinions about the success of chemotherapy regimens with curative or inductive intent in patients with early stage laryngeal carcinoma. In this case report, a patient with T2N0M0 squamous cell carcinoma of the supraglottic larynx who presented with local recurrence and regional metastasis after a 54 months of non-followed period which follows two courses of cisplatinum/5-FU induction chemotherapy alone was presented. The beneficial effects of the induction chemotherapy in patients with early stage laryngeal carcinoma are doubtful. However, this regimen may be useful to estimate the possible success of radiotherapy by counseling with the patients who initially refused the conservative partial laryngectomy and with their families.